Current Design and Performance of Cold Spray Nozzles: Experimental and Numerical Observations on Deposition Efficiency and Particle Velocity - LUPOI, ROCCO (My University, 2014)
Coating technologies play a critical role in the worldwide manufacturing industry. The ability to form layers of specific materials onto engineering components to enhance mechanical and physical properties has numerous applications, ranging from corrosion protection, repair, hardfacing, down to purely aesthetic purposes. Cold spray is an innovative technology, which allows for the manufacturing of coatings in a solid state manner; hence, feedstock properties can be fully preserved. Its working principles relies upon the acceleration of powders up to supersonic velocities, and the subsequent generation of high energy impacts on a substrate which triggers the coating formation. This paper presents deposition efficiency (DE) results from four different supersonic nozzles when using titanium as feedstock material. DE is the most critical parameter to assess the performance of cold spray nozzles. A theoretical analysis through computational fluid dynamics (CFD) is carried out so to compare numerical results against experimental findings. Results have suggested that current commercial codes cannot accurately predict the acceleration process under realistic working conditions. It is therefore difficult to predict DE levels. Cold Spray is starting to be applied to high end engineering; however, it is likely not to be successful unless critical understanding is generated and used to accurately design nozzles, and predict the performance of new prototypes.
Keywords: Nozzle design; Deposition efficiency; Particle velocity; CFD; Titanium coatings; Cold spray